Tension‐Induced Raman Enhancement of Graphene Membranes in the Stretched State. Issue 2 (3rd December 2018) - Hu, Kai‐Ming; Xue, Zhong‐Ying; Liu, Yun‐Qi; Long, Hu; Peng, Bo; Yan, Han; Di, Zeng‐Feng; Wang, Xi; Lin, Liwei; Zhang, Wen‐Ming
Abstract: The intensity ratio of the 2D band to the G band, I 2D / I G, is a good criterion in selecting high quality monolayer graphene samples; however, the evaluation of the ultimate value of I 2D / I G for intrinsic monolayer graphene is a challenging yet interesting issue. Here, an interesting tension‐induced Raman enhancement phenomenon is reported in supported graphene membranes, which show a transition from the corrugated state to the stretched state in the vicinity of wells. The I 2D / I G of substrate‐supported graphene membranes near wells are significantly enhanced up to 16.74, which is the highest experimental value to the best of knowledge, increasing by more than 600% when the testing points approach the well edges.The macroscopic origin of this phenomenon is that corrugated graphene membranes are stretched by built‐in tensions. A lattice dynamic model is proposed to successfully reveal the microscopic mechanism of this phenomenon. The theoretical results agree well with the experimental data, demonstrating that tensile stresses can depress the amplitude of in‐plane vibration of sp 2 ‐bonded carbon atoms and result in the decrease in the G band intensity. This work can be helpful in furthering the development of the method of suppressing small ripples in graphene and acquiring ultraflat 2D materials. Abstract : An interesting tension‐induced Raman enhancement phenomenon, where the intensity ratios I 2D / I G are significantly enhanced up to 16.74 and increased by more than 670%, is observed in substrate‐supported graphene membranes near the wells. The microscopic mechanism of this phenomenon is the depression effect of built‐in stresses on the intensity of the G band.